Passing on the half-empty glass: A transgenerational study of interpretation biases in children at risk for depression and their parents with depression - Sfärlea, Anca; Löchner, Johanna; Neumüller, Jakob; Thomsen, Laura Asperud; Starman, Kornelija; Salemink, Elske; Schulte-Körne, Gerd; Platt, Belinda (Journal of Abnormal Psychology, 2019)
Children of parents with a history of depression have an increased risk of developing depression themselves. The present study investigated the role of interpretation biases (that have been found in adults and adolescents with depression but have rarely been examined in at-risk youth) in the transgenerational transmission of depression risk. Interpretation biases were assessed with two experimental tasks: Ambiguous Scenarios Task (AST) and Scrambled Sentences Task (SST) in 9-14-year-old children of parents with a history of depression (high risk; n = 43) in comparison to children of parents with no history of mental disorders (low risk; n = 35). Interpretation biases were also compared between the two groups of parents and relationships between children's and parents' bias scores were examined. As expected, we found more negative interpretation biases in high-risk children compared to low-risk children as well as in parents with a history of depression compared to never-depressed parents (assessed via the SST but not the AST). However, transgenerational correlations were only found for the AST. Our results indicate that negative interpretation biases are present in youth at risk for depression, possibly representing a cognitive vulnerability for the development of depression. Moreover, different measures of interpretation bias seemed to capture different aspects of biased processing with the more implicit measure (SST) being a more valid indicator of depressive processing.
CRIS-Team Scopus Importer:2024-11-26
Keywords: Ambiguous Scenarios Task; Interpretation bias; Parental depression; Scrambled Sentences Task; Transgenerational transmission